MAM-mediated mitophagy and endoplasmic reticulum stress: the hidden regulators of ischemic stroke - Jia, Ziyi; Li, Hongtao; Xu, Ke; Li, Ruobing; Yang, Siyu; Chen, Long; Zhang, Qianwen; Li, Shulin; Sun, Xiaowei (Frontiers in Cellular Neuroscience, 2024)
Ischemic stroke (IS) is the predominant subtype of stroke and a leading contributor to global mortality. The mitochondrial-associated endoplasmic reticulum membrane (MAM) is a specialized region that facilitates communication between the endoplasmic reticulum and mitochondria, and has been extensively investigated in the context of neurodegenerative diseases. Nevertheless, its precise involvement in IS remains elusive. This literature review elucidates the intricate involvement of MAM in mitophagy and endoplasmic reticulum stress during IS. PINK1, FUNDC1, Beclin1, and Mfn2 are highly concentrated in the MAM and play a crucial role in regulating mitochondrial autophagy. GRP78, IRE1, PERK, and Sig-1R participate in the unfolded protein response (UPR) within the MAM, regulating endoplasmic reticulum stress during IS. Hence, the diverse molecules on MAM operate independently and interact with each other, collectively contributing to the pathogenesis of IS as the covert orchestrator.